Bioestratigrafía de conodontes del ordovícico medio–superior de la precordillera oriental, San Juan, Argentina - Heredia, Susana (2024)
The La Cantera Formation is a siliciclastic unit with restricted distribution that crops out at the eastern edge of the Villicum range (Eastern Precordillera), province of San Juan, Argentina. Its age has previously been recorded based on index graptolites. Several conglomerate, sandstone, and mudstone samples were collected from the lower and middle members of the La Cantera Formation, which provided conodonts and other microfossils such as ostracoderm plates, gastropods, bryozoans, and fragmented brachiopod shells. The retrieved conodont fauna is poorly diverse and just appears as casts in the mudstone bedding planes. It is composed mostly of elements of the genus Eoplacognathus that were recovered from sandstone units and elements of the genus Pygodus that appear as casts in the mudstone units. In addition, elements of the genera Baltoniodus, Pygodus, Periodon, and Erismodus among others, were retrieved from sandstone units. The conodont associations allow proposing, for the first time, a Middle-Upper Ordovician biostratigraphy for the Eastern Precordillera which includes three conodont zones and subzones, in ascending order: Lenodus suecicus Zone (Pygodus anitae Subzone), Pygodus serra Zone (Eoplacognathus robustus Subzone), and Pygodus anserinus Zone (Upper Subzone). This new biostratigraphic information provides an accurate correlation of this classic unit from the Eastern Precordillera with other units from the Central Precordillera. Also, the recognition of several hiatuses in different time intervals reveals the instability of the basin during the late Darriwilian early Sandbian.